Research on the Countermeasures of Digital Technology to Optimize Enterprise Cost Management - Yang, Changpeng (International Journal of Global Economics and Management, 2024)
In the cost control process of enterprises, the use of digital means can efficiently integrate the resources of enterprises, strengthen the collaborative work between various departments, accelerate the speed of information transmission, promote innovation activities, improve economic benefits, and optimize the efficiency of cost management. Following the core concept of fine cost control and under the extensive influence of digital economy, this paper explores the way of optimizing cost management by visiting modern enterprises on the spot. This paper expounds the connotation of digital economy and cost management, and provides theoretical support for the subsequent analysis. Then, it analyzes the challenges and opportunities faced by enterprises in the field of cost management under the background of digital economy. Finally, it analyzes many problems existing in the actual operation of cost management of enterprises, and puts forward some specific measures to improve cost management, aiming at helping enterprises to improve production efficiency, reduce cost expenses, and explore market potential.